Perlindungan Hukum Bagi Kreditur Akibat Wanprestasi Dalam Perjanjian Pinjam Meminjam Dengan Jaminan Benda Bergerak Milik Pihak Ketiga - Permana, Yudhistira Gilang; Marsitiningsih, Marsitiningsih (JURNAL PENELITIAN SERAMBI HUKUM, 2025)
Lending and borrowing agreements secured by movable objects owned by third parties have become a complexlegal phenomenon,especially when there is a default by the debtor. In practice,many creditors suffer losses dueto ignorance or negligence in verifying the legal status of the collateral object. This research aims to analyze theform of legal protection for creditors and the legal procedures that can be taken in the event of default in theagreement. The method used is normative legal research with a statutory approach and legal literature.Theresults of the study show that legal protection for creditors in this case is regulated in several legal provisions,including Article 1320 and Article 1365 of the Civil Code (KUHPerdata), as well as Article 15 paragraph(2)ofLaw Number 42 of 1999 concerning Fiduciary Guarantees, which gives executorial rights to creditors with thesame power as court decisions that have been legally enforceable (inkracht). the importance of the principle ofprudence, the validity of documents, and the involvement of notaries in strengthening the legal position ofcreditors. Alternative dispute resolution such as mediation, subpoena, and execution of collateral through legalchannels are important means of protection for creditors. Article 29 of Law Number 42 Year 1999 on FiduciaryGuarantee. Every form of settlement must be based on the principles of legality, good faith, and prudence(prudential principle), and payattention to the rights of third parties in good faith. Efforts taken by creditors dueto default in a loan agreement with movable object collateral are carried out through two channels,namelylitigation and non-litigation. The litigation path is a settlement taken through the court, this path is formal,procedural, and the results are binding aind have permanent legal force. Non-litigation settlement is a legal effortoutside the court that is valid according to positive law and based on the principles of freedom of contract andgood faith. Keywords:legal protection,creditor,default